Pattern of non-obstetric infectious recto-vaginal fistula: a case series and literature review in Cameroon, Central Africa - Tebeu, Pierre Marie; Ekono, Roger Guy Michel; Fouogue, Jovanny Tsuala; Halle, Gregory Ekane; Fokom, Joel Domgue; Rochat, Charles Henry (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Perineal infection is an uncommon cause of non-obstetrical recto-vaginal fistula (RVF) which is associated with HIV infection. Cameroon (Central Africa) is in the fistula belt but infectious RVFs have not yet been deeply studied in the country. We therefore sought to determine the pattern of non-obstetric infectious RVF in Cameroon. Methods: We carried out a cross-sectional and descriptive review of non-obstetric infectious RVFs managed at the Yaoundé University Teaching Hospital between January 1, 2009 and December 31, 2015. All complete files were included. The following data were retrieved: socio-demographics, characteristics of the RVF, management and outcome. Results: Five non-obstetrical and non-traumatic RVFs of which four were observed in HIV-infected patients were included. All those RVFs occurred spontaneously. The following predisposing factors were identified: perineal warts (one case out of five), perineal suppuration (two cases out of five), hemorrhoids (the HIV-negative patient), spinsterhood (all cases), unemployment (all cases). All HIV-patients were under anti-retroviral therapy (ART) with good immunological and clinical responses for three of them. Three of them underwent previous unsuccessful surgical cure. Management included ART, antibiotics and surgery. Surgical approaches were perineotomy alone or with martius’ flap, procto-perineotomy or trans-vaginal advancement flap. Outcome was satisfactory for all HIV patients (closure of fistula and fecal continence). Conclusions: Local infection is a rare cause of RVF which was associated with HIV in our series. Combined treatment including antibiotics, HAART and surgery gave good results.